A Closer Look at Sectoral Financial Linkages in Brazil I : Corporations' Financial Statements - Karpowicz, Izabela (IMF Working Papers; Working Paper ;, 2016)
Understanding the interplay between firms' balance sheets and the macro-economic environment is important for understanding of the Brazilian economy. A close examination of developments in the nonfinancial corporate sector up to the early 2015 reveals weak equity growth, declining profitability, and rising leverage. The empirical work suggests that adverse shocks to financial variables lead to weaker real GDP growth in Brazil through their effect on corporate leverage, borrowing costs, and default frequencies. An estimation based on a DSGE model with financial frictions indicates that the recent economic downturn in Brazil is largely driven by a decrease in total factor productivity and by negative financial shocks.